Respuesta :
Answer:
12x+3y+3
Step-by-step explanation:
Let's simplify step-by-step.
4x+2y+6+7x+3y−4+x−2y+1
=4x+2y+6+7x+3y+−4+x+−2y+1
Combine Like Terms:
=4x+2y+6+7x+3y+−4+x+−2y+1
=(4x+7x+x)+(2y+3y+−2y)+(6+−4+1)
=12x+3y+3
Answer:
12x + 3y + 3
General Formulas and Concepts:
Algebra I
- Combining Like Terms
Step-by-step explanation:
Step 1: Define
(4x + 2y + 6) + (7x + 3y - 4) + (x - 2y + 1)
Step 2: Simplify
- Combine like terms (x): 12x + 2y + 6 + 3y - 4 - 2y + 1
- Combine like terms (y): 12x + 3y + 6 - 4 + 1
- Combine like terms (Z): 12x + 3y + 3